INVENTORY MANAGEMENT ON HASKE SWEET COMPANY - Umar Mohammed Ali (Frontline Marketing, Management and Economics Journal, 2021)
As the most important part of a company’s current assets, effective inventory management is not easy especially in a manufacturing enterprise where inventory management plays a great rule in the survival of a company. The most difficult task in inventory management is to determine the optimum level of inventory and also appraise a decision rule for ordering inventory in the right quantity and at the right time. This will ensure the management to avoid the holding cost and the Out of stock cost. The inventory item of Haske sweet and confectionery Nigerian Ltd, Maiduguri include, raw materials, stock of finished goods and the inventory of suppliers item (i.e stationeries, spare parts etc). Each of the above inventory plays a significance role to the survival and continuous operation of the company under study. To ensure effective inventory control in the Haske sweet various techniques like minimum – maximum system of contract Economic order quantity (EOQ) method for estimating the quantity to order in a given period of time and Bin card system of control are used in the company.